The Influence of Double Loop Problem Solving (DLPS) Technique to Teach Reading Comprehension Achievement of The Tenth Grade Students of SMA Negeri 1 Belitang Jaya - Risa, Risakristia; Kuspiyah, Hastuti Retno; Muklas, Muhamad (ENJEL: English Journal of Education and Literature, 2022)
This thesis is entitled “The Influence of Double Loop Problem Solving (DLPS) Technique to Teach Reading Comprehension Achievement of The Tenth Grade Students of  SMA Negeri 1 Belitang Jaya". The objective  was find out whether or not there is any significance difference between the students who are taught by using Double Loop Problem Solving technique and the students who are taught by using conventional technique to teach reading comprehension achievement at the tenth grade students of SMA N 1 Belitang Jaya. The method of the study used quantitative research, and quasi experimental design. Therefore, there were two groups those were experimental group who are taught by using Double Loop Problem Solving technique and control group who are taught by using conventional technique, that was chosen by using purposive sampling to collecting the data, the population of this study were 120 students and sample were 60 students. The study was used multiple choice test as an instrument for collecting the data. The data obtained from Independent t-test analysis by using SPSS 25, between the result of post-test in experimental group and control group. Based on the calculation by using Independent t-test in SPSS 25, the writer found that value of t-obtained is 4.906. with 5% sig. level for 2-tailed was 0.001(0.001 < 0.05), and the critical value t-table is 2.001. it showed that t-obtained was higher than t-table (4.906 > 2.001). So, the null hypotheses (Ho) was rejected and alternative hypotheses (Ha) was accepted. It can be concluded that Double Loop Problem Solving technique was significant to teach reading comprehension achievement at the tenth grade students of SMA N 1 Belitang Jaya.